The alpha-eta transformation in cobalt with particular reference to the use of cobalt in cemented carbides - Rees, G J (My University, 2015)
A study of the reduction of black cobalt oxide, using hydrogen as the reductant, showed that the temperature and time used for reduction exerted a profound influence on the proportions of face centred cubic (a) and hexagonal close packed (e) cobalt allotropes obtained in the reduced metal powder. Reduction under certain conditions yielded a faulted hexagonal cobalt powder product which contained stacking faults. The influence of oxygen and titanium on cobalt materials showed that these impurities did not stabilise the proportions of either the cubic or hexagonal phases under the conditions, which were used. The grinding of cobalt powders from different sources showed different tendencies towards agglomeration, when acetome was used as the milling fluid. It was found that powders which contained an initially higher proportion of the hexagonal phase -had a strong tendency towards agglomeration during the initial stages of grinding. The importance of the different phases of cobalt present in the metal powders, and their different agglomeration tendencies on grinding, on the milling required for satisfactory densification of cobalt - tungsten carbide compacts has been shown; it was (iv) found that hard metal alloys prepared using powders with an initially higher proportion of the hexagonal phase required less milling to achieve a given sintered density, than did mixtures prepared with other cobalt powder*;. A correlation analysis between the properties of the milled hard metal powders and the properties of the sintered compacts was carried out; it was found that the most important correlation was between the specific surface area of the milled hard metal powder and the coercivity of the sintered product.
Keywords: Cobalt; Carbides